2014
DOI: 10.5603/ait.2014.0051
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and knowledge of intra-abdominal hypertension and abdominal compartment syndrome: results of an international survey

Abstract: This survey showed that although most responding clinicians claim to be familiar with IAH and ACS, knowledge of published consensus definitions, measurement techniques, and clinical management are inadequate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 29 publications
0
15
0
1
Order By: Relevance
“…Intra-abdominal hypertension (IAH) is defined as a sustained increase in intra-abdominal pressure (IAP) equal to or above 12 mmHg [1]. Critical care physicians around the world still underestimate the high incidence of IAH which is around 25% in mixed ICU patients [2, 3].…”
Section: Introductionmentioning
confidence: 99%
“…Intra-abdominal hypertension (IAH) is defined as a sustained increase in intra-abdominal pressure (IAP) equal to or above 12 mmHg [1]. Critical care physicians around the world still underestimate the high incidence of IAH which is around 25% in mixed ICU patients [2, 3].…”
Section: Introductionmentioning
confidence: 99%
“…Intra-abdominal pressure is an important physiological parameter that is still often neglected by the medical community [4]. It should be measured regularly in critically ill patients, 4 to 6-hourly, according to the guidelines [1].…”
Section: Discussionmentioning
confidence: 99%
“…Although the first cases of ACS were described decades ago, interest has recently increased exponentially. Nevertheless, a recent survey demonstrated that knowledge among physicians is still suboptimal toward clinical management and awareness of ACS [ 2 ].…”
Section: Introductionmentioning
confidence: 99%